1973
DOI: 10.1126/science.182.4107.83
|View full text |Cite
|
Sign up to set email alerts
|

Student Ratings of Teaching: Validity of Several Rating Factors

Abstract: Students' ratings of their instructors in undergraduate classes in calculus were correlated with class performance on a common final examination. Ratings on several instructional factors were highly related to class performance even though they appeared to be independent of the students' own grades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
3
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 3 publications
2
70
3
1
Order By: Relevance
“…Also of importance in validity analyses is an analysis of the means. Table 8 presents the means reported by the three studies: Benton and Scott (1976), Endo andDella-Piana (1976), andFrey (1973).…”
Section: Analysis Of the Meansmentioning
confidence: 99%
See 4 more Smart Citations
“…Also of importance in validity analyses is an analysis of the means. Table 8 presents the means reported by the three studies: Benton and Scott (1976), Endo andDella-Piana (1976), andFrey (1973).…”
Section: Analysis Of the Meansmentioning
confidence: 99%
“…All but four of the studies included in Cohen's analysis were obtained (Crooks & Smock, 1974;Reynolds & Hansvick, 1978;Spencer & Dick, 1965;Wherry, 1952; all of which were unpublished studies). Of the obtained studies from Cohen and Clayson, it was found that three reported mean student ratings and final exam score means (Benton & Scott, 1976;Endo & Della-Piana, 1976;Frey, 1973). These means were included by the authors of these studies, but the authors did not analyze them or refer to them as being important.…”
Section: Overall Instructor Rating With Student Achievementmentioning
confidence: 99%
See 3 more Smart Citations